2009
DOI: 10.1007/s12272-009-1807-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nrf2-mediated heme oxygenase-1 upregulation in adaptive survival response to nitrosative stress

Abstract: Nitrosative stress caused by reactive nitrogen species such as nitric oxide and peroxynitrite overproduced during inflammation leads to cell death and has been implicated in the pathogenesis of many human ailments. However, relatively mild nitrosative stress may fortify cellular defense capacities, rendering cells tolerant or adaptive to ongoing and subsequent cytotoxic challenges, a phenomenon known as 'preconditioning' or 'hormesis'. One of the key components of cellular stress response is heme oxygenase-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 96 publications
2
73
0
1
Order By: Relevance
“…NF-E2-related factor (Nrf2) is responsible for the activation of ARE-driven antioxidant gene expression (14). Recent studies have demonstrated that the activation of the mitogen-activated protein kinases (MAPKs) contributes to the induction of HO-1 and the modulation of ARE-driven gene expression via Nrf2 activation (15).…”
Section: Introductionmentioning
confidence: 99%
“…NF-E2-related factor (Nrf2) is responsible for the activation of ARE-driven antioxidant gene expression (14). Recent studies have demonstrated that the activation of the mitogen-activated protein kinases (MAPKs) contributes to the induction of HO-1 and the modulation of ARE-driven gene expression via Nrf2 activation (15).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the inhibition of HO-1 induction and that of the antiinflammatory effect of acteoside by SB203580 suggests that p38 plays a key role in acteoside-mediated HO-1 induction. The HO-1 gene promoter contains multiple regulatory transcription factor binding sites, including ARE, NF-κB, AP-1, and AP-2 responsive elements (Boberek et al, 2010;Lavrovsky et al, 1994;Surh et al, 2009). Among the transcriptional factors, Nrf2 is the transcription factor that can activate the transcription of anti-oxidant proteins including HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…It also was recently reported that the HO-1 system provides a therapeutic effect in many experimental pathological conditions (Bonelli et al, 2012;Farombi and Surh, 2006;Luz et al, 2012). In oxidative injury and inflammation conditions, an increase in the synthesis of the HO-1 gene is linked to the transcription factors NFkB, Nrf2, and AP-1 (Paine et al, 2010;Srisook et al, 2005;Surh et al, 2009). Among the transcriptional factors, Nrf2 nuclear translocation requires the activation of several signal transduction pathways, such as mitogen-activated protein kinases (MAPKs), phosphatidylinositol 3-kinase (PI3K) and0 Akt (Martin et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Many previous studies have shown that Nrf2 is involved in the transcriptional regulation of the HO-1 gene (Surh et al, 2009). If a cell experiences oxidative stress, Nrf2, the transcriptional factor for antioxidant responsive element (ARE), is liberated from Keap1 with subsequent translocation of Nrf2 to the nucleus.…”
Section: Discussionmentioning
confidence: 99%